56-month clinical performance of Class I and II resin composite restorations - Flavia Bittencourt Pazinatto; Ranulfo Gionordoli Neto; Linda Wang; José Mondelli; Rafael Francisco Lia Mondelli; Maria Fidela de Lima Navarro (University of São Paulo, 2012)
OBJECTIVE: This study evaluated the 56-month clinical performance of Class I and II resin composite restorations. Filtek P60 was compared with Filtek Z250, which are both indicated for posterior restorations but differ in terms of handling characteristics. The null hypothesis tested was that there is no difference in the clinical performance of the two resin composites in posterior teeth. MATERIAL AND METHODS: Thirty-three patients were treated by the same operator, who prepared 48 Class I and 42 Class II cavities, which were restored with Single Bond/Filtek Z250 or Single Bond/Filtek P60 restorative systems. Restorations were evaluated by two independent examiners at baseline and after 56 months, using the modified USPHS criteria. Data were analyzed statistically using Chi-square and Fisher's Exact tests (a=0.05). RESULTS: After 56 months, 25 patients (31 Class I and 36 Class II) were analyzed. A 3% failure rate occurred due to secondary caries and excessive loss of anatomic form for P60. For both restorative systems, there were no significant differences in secondary caries and postoperative sensitivity. However, significant changes were observed with respect to anatomic form, marginal discoloration, and marginal adaptation. Significant decreases in surface texture were observed exclusively for the Z250 restorations. CONCLUSIONS: Both restorative systems can be used for posterior restorations and can be expected to perform well in the oral environment.